From the Guest Editors - Carlos Castillo-Chávez; Christopher Kribs Zaleta; Yang Kuang; Baojun Song (Mathematical Biosciences and Engineering)
Those of us who met the field of mathematical biology as a well-developed,flourishing, and rewarding discipline owe much to those who made it so.This special issue of Mathematical Biosciences and Engineering isdedicated to two such pioneers: Fred Brauer and Karl Hadeler.Since retrospectives of both men have been published in other venues [1, 2], we will only summarize their contributions briefly here.Fred Brauer obtained his Ph.D. from MIT in 1956 under Norman Levinson,and during a long tenure at the University of Wisconsin he co-wrote severaltexts on ordinary differential equations that have become classics.His research entered mathematical biology first through early studies inpredator-prey systems and harvesting, both with and without delays.He then moved into mathematical epidemiology, and the text he co-authoredwith Carlos Castillo-Chavez in both these areas earlier this decade isalready in wide use.For more information please click the “Full Text” above.